How to Speak Money : What The Money People Say -- And What They Really Mean - Lanchester, John (London : Faber & Faber, 2014)
Money is our global language. Yet so few of us can speak it. The language of the economic elite can be complex, jargon-filled and completely baffling. Above all, the language of money is the language of power - power in the hands of the same economic elite.Now John Lanchester, bestselling author of Capital and Whoops! sets out to decode the world of finance for all of us, explaining everything from high-frequency trading and the World Bank to the difference between bullshit and nonsense.As funny as it is devastating, How To Speak Money is a primer and a polemic. It's a reference book you'll find yourself reading in one sitting. And it gives you everything you need to demystify the world of high finance - the world that dominates how we all live now.
Includes bibliographical references (pages 283-286).
Keywords: Economics -- Terminology